Job satisfaction towards employee retention among private sector employees in Sibu, Sarawak, Malaysia - Wong, Sophia Wang Szu (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This paper is designed to understand the job satisfaction towards employee retention among private sector employee in Sibu, Sarawak, Malaysia. Data was collected through questionnaire among private company in Sibu. The data were analysed by using Statistical Package for Social Science (SPSS) version 17.0 for Microsoft Windows The intrinsic job satisfaction factors have been found to be able to significantly affect the employee retention of private company in Sibu, Sarawak, Malaysia.